Pronounced Segregation of Donor Mitochondria Introduced by Bovine Ooplasmic Transfer to the Female Germ-Line - Ferreira, Christina Ramires [UNESP]; Burgstaller, Joerg Patrick; Perecin, Felipe [UNESP]; Garcia, Joaquim Mansano [UNESP]; Chiaratti, Marcos Roberto; Meo, Simone Cristina [UNESP]; Mueller, Mathias; Smith, Lawrence Charles; Meirelles, Flavio Vieira; Steinborn, Ralf (Soc Study Reproduction, 2010)
Ooplasmic transfer (OT) has been used in basic mouse research for studying the segregation of mtDNA, as well as in human assisted reproduction for improving embryo development in cases of persistent developmental failure. Using cattle as a large-animal model, we demonstrate that the moderate amount of mitochondria introduced by OT is transmitted to the offspring's oocytes; e. g., modifies the germ line. The donor mtDNA was detectable in 25% and 65% of oocytes collected from two females. Its high variation in heteroplasmic oocytes, ranging from 1.1% to 33.5% and from 0.4% to 15.5%, can be explained by random genetic drift in the female germ line. Centrifugation-mediated enrichment of mitochondria in the pole zone of the recipient zygote's ooplasm and its substitution by donor ooplasm led to elevated proportions of donor mtDNA in reconstructed zygotes compared with zygotes produced by standard OT (23.6% +/- 9.6% versus 12.1% +/- 4.5%; P < 0.0001). We also characterized the proliferation of mitochondria from the OT parents-the recipient zygote (Bos primigenius taurus type) and the donor ooplasm (B. primigenius indicus type). Regression analysis performed for 57 tissue samples collected from the seven OT fetuses at different points during fetal development found a decreasing proportion of donor mtDNA (r(2) = 0.78). This indicates a preferred proliferation of recipient taurine mitochondria in the context of the nuclear genotype of the OT recipient expressing a B. primigenius indicus phenotype.
Keywords: Bovine; developmental biology; Embryo; gamete biology; Mitochondrial DNA; ooplasmic transfer